DIGITAL LITERACY, BUSINESS UNCERTAINTY AND SUSTAINABILITY BUSINESS: A DESCRIPTIVE ANALYSIS - M. Adhi Prasnowo; Eddy Yunus, Meithiana Indrasari (CV. Adiba Aisha Amira, 2025)
This research aims to examine the preliminary data of research results that examine the model of strengthening the understanding of digital literacy can have an impact on sustainability business in conditions of business uncertainty. This research examines with a descriptive approach. The data collection technique used in this research is a questionnaire. This study uses a questionnaire used to collect data related to variables that will later be processed. Descriptive analysis of the research data review that has been carried out shows that with the demographic conditions of the respondents, the majority of respondents in this study are women with a percentage of 61.2%. While men are only 38.8%. Respondents with DEA training 98.7% while respondents with TA training 1.3%. The type of respondent's business consists of culinary 44.6%, services 13.9%, fashion 11.4%, tour & travel, Creative Products 3.9%, Internet Technology 3.1%, Agribusiness 2.8%, others 20.3%. Furthermore, it can provide an overview of the results that in the digital literacy variable, respondents consider that